Chemosynthesis and characterization of site-specific N-terminally PEGylated Alpha-momorcharin as apotential agent. Issue 1 (December 2018) - Sun, Wenkui; Sun, Jinghui; Zhang, Haowen; Meng, Yanfa; Li, Linli; Li, Gangrui; Zhang, Xu; Meng, Yao
Abstract Alpha-momorcharin (α-MC), a type I ribosome-inactivating protein (RIP) isolated fromMomordica charantia seeds, has been extensively studied for its antitumor, antiviral and antifungal activities. However, as an exogenous protein, problems associated with short half-life and strong immunogenicity have limited its clinical application. Poly (ethylene glycol) (PEG), as a polyether compound, is a well established and efficient modifier to develop it as a potential agent. Nevertheless, conventional PEGylation is not site-controlled and the conjugates are often not homogenous due to the generation of multi-PEGylated derivatives. To obtain a homogenous mono-PEGylated α-MC, the PEGylation was carried out by coupling a 20 kDa mPEG-butyraldehyde (mPEG-ALD) with α-MC. The product was separated and purified by MacroCap SP chromatography. Results from SDS-PAGE and MALDI-TOF MS revealed that the PEGylated α-MC consisted of one molecule mPEG and α-MC. Edman degradation confirmed that theN -terminal residue of α-MC was successfully coupled with mPEG-ALD. The mono-PEGylated α-MC possessed an extremely similar secondary structure to native α-MC through spectral analyses. In addition, it also showed low immunogenicity by double immunodiffusion and preserved moderate antitumor activity to three kinds of tumor cell linesin vitro . Finally, trypsin resistance was also considerably improved.